Efek Proses Pengolahan Terhadap Kadar Fenol, Vitamin C dan Penerimaan Konsumen pada Teh Daun Tatat (Bauhinia acuminata) - Fitriarni, Dian (Swiss German University & Perhimpunan Penggiat Pangan Fungsional dan Nutrasetikal Indonesia (P3FNI), 2023)
Human awareness to maintain health provides an increase in consumption of natural products. This requires various efforts to explore natural products and process them into functional food. Herbal tea is one type of functional food from plant are produces in form dried herbs plant. Tatat leaves is rich in bioactive compounds such as alkaloid and polyphenols. This are actually quite well known in Sandai, which are believed to treat heat, lower blood sugar, hypertension, and immunomodulators. The purposes of this study is to make tatat leaf tea as functional food products with good quality especially for compotition and consumer preference using 2 different drying methods. Based on the results, it was found that visually the color produced by tatat leaves from the processing results was brighter with a brownish orange color, in contrast to tatat leaves which were brewed without processing which resulted in a pale yellow color. Based on the results of hedonic analysis, panelists prefer the taste, aroma, and color of tatat leaves from the processing treatment. The results of the analysis of phenol levels showed that the tatat leaves tea from the processing process was 91.078 mgGAE / g higher than the tatat leaves tea without processing 40.643 mgGAE / g. The results of the vitamin C test showed that the percentage of tatat leaves tea from the processing process was lower at 29.74 mg / 100 g compared to the tatat leaves from the direct drying method of 44.92 mg / 100 g.